A situação de comunicação dos Akwẽ-Xerente surdos - Barretos, Euder Arrais (2016)
This research aims to investigate the situation of communication in which the Akwẽ-Xerente Deaf people are situated. In view of its execution, it has become relevant the identification, the registration, the description and the analysis of the communicative situation in which they are inserted, considering the reports of the research collaborators on the communicative interactions between Deaf-Deaf and Deaf-listener, among other factors inherent to the communication process of the Deaf in the cultural ambiance of this people. Regarding research methodology, we considered making use of qualitative approaches (DENZIN, LINCOLN, 2006; LÜDKE, ANDRÉ, 1986) and quantitative approaches, a bibliographical research, surveys and a field study. For the generation of data, we adopted, in addition to the bibliographical research, observation and personal conversations collected during the Intercultural and Transdisciplinary Specialization offered by Universidade Federal de Goiás (UFG) as well as the moments of my fieldwork in Akwẽ villages, and semi-structured interviews with Akwẽ teachers attending that course. The theoretical foundations that supported the research were, among others, the concept of deafness as a cultural difference coined by Skliar (2005), rooted in socio-anthropological theories and theories of mediations or culturalist theories of communication and the notions of utterances based on Bateson (2002), Martin-Barbero (1991), Bakhtin (1997) and Freire (1987). As for sociolinguistic analysis of Akwẽ-Xerente, we considered the data generated from the studies by Lopes and Farias (1992), Guimarães (2002), Schroeder (2010), Cotrim (2011), Mesquita (2015) and my field research. The survey recorded the presence of thirteen Deaf people between the ages 07 and 62 years old living in 10 villages of this people and the research evidenced the ways of seeing and being in the world of the Akwẽ-Xerente people. It also showed the forms of communication between Deaf-Deaf and Deaf-listener, as well as the access the Deaf have to the cultural practices of their people. It is evident from this study the great possibility of communicative interaction provided by the cultural practices of Akwẽ-Xerente and, on the other hand, the need to further investigate the communication between Deaf-listener and Deaf-Deaf, considering the spaces of cultural production and the use of signs as well as the discussion of the "homemade signs" and the concept of language discussed by other studies regarding the indigenous Deaf in Brazil. The access to knowledge, to the wisdom that is already available to all in the cultural life-experiences of this people should also be considered in the educational process by the means of the use of visuals, images and rituals that, when authorized, can be experienced, learned and internalized by all without the exclusive use of oralism necessarily. In this understanding, the appropriation and the dissemination by Akwẽ sign language school brought by the Deaf are essential to expand the possibilities of communication among everyone, to the cultural valorization and the improvement of selfesteem. For the inclusion of Deaf people in Akwẽ schools, we should take into account all these world records and all this form of communication. In this respect, while we highlight the presence of Akwẽ signs, we ask ourselves about the existence of a Akwẽ-Xerente sign language.